ChemInform Abstract: Efficient Ring Opening Reaction of Epoxides with Oxygen Nucleophiles Catalyzed by Quaternary Onium Salt. Issue 50 (10th December 2013) - Kim, Jin Won; Cho, Dae Won; Park, Gyoosoon; Kim, Sung Hong; Ra, Choon Sup
Abstract The quarternary phosphonium salt Bu4PBr shows to be the most efficient catalyst for the title ring opening reaction.